Greetings from Chile - Bravo, Úrsula (FormAkademisk, 2023)
I met Liv Merete Nielsen at the DRS Limerick 2018 conference. I was studying Chilean teachers' use of design methods to solve pedagogical problems supported by a British Council fund. Peter Lloyd and Derek Jones brought the experience and vision of The Open University's Design Thinking course. They had Nigel Cross as an unavoidable theoretical reference. I also knew Maureen Carroll and Shelley Goldman's work at Stanford University to promote STEM disciplines in vulnerable schools in Palo Alto. Maureen and Shelley built on the IDEO-d.School universe and had Tim Brown and David Kelly as key references.